Post-Pandemic Society: Case Study of Gunungkidul Regency in Digital Tourism Transformation - Adinda Aulia Hafizha; Hanifah Fadhilah; Innayah Yanwari; Diaz Prameswara; Nisaul Fariziyah Azziyad; Sophiana Widiastutie (Randwick International of Social Science Journal, 2023)
This study aims to determine the government’s role and the digitalization process in the Gunungkidul tourism sector and its impact on the surrounding community after the COVID-19 pandemic. Using a qualitative research method with case study approach, data is collected through literature studies of relevant articles, documents, and scientific works to then carry out an in-depth interpretation analysis. The results of the study show that the Gunungkidul government's digitization program which consists of the #IniGunungKidul - The Ultimate Hidden Gem campaign, the regional digitalization acceleration program through a digital economic ecosystem, and training for business actors has achieved excellent success. Throughout 2022, there has been an increasing trend of Gunungkidul tourists and in the same year, the poverty rate for the Gunungkidul has decreased by 2% compared to the previous year. It can be concluded that the government's consistency in implementing digitization of tourism can restore the Gunungkidul economy and at the same time creating a new, technologically literate post-pandemic society.